Magnetic Characteristics of Soil in Cocoa and Cashew Production Fields Using the Magnetic Susceptibility Method - Arisona A. (Jurnal Rekayasa Geofisika Indonesia, 2023)
Soil magnetic characteristics on land under stands of cacao and cashew trees were carried out by varying the depth. This soil magnetic determination uses the magnetic susceptibility method. The results indicated that the magnetic characteristics of the soil under tree stands depended on the frequency ( ) and the frequency-dependent susceptibility value ( with an increase towards the top of the soil profile in cocoa and cashew trees. This condition causes the formation of higher minerals as a result of changes in the size of the smaller grains that increase towards the upper horizon. The measured magnetic susceptibility value shows that the soil magnetic characteristics of the two tree species are Paramagnetic. The difference in magnetic susceptibility values ​​which tend to be high indicates that the contribution of superparamagnetic minerals is the result of the pedogenesis process